Pathophysiology and Diagnosis of Coronary Functional Abnormalities - Jun Takahashi; Akira Suda; Kensuke Nishimiya; Shigeo Godo; Satoshi Yasuda; Hiroaki Shimokawa (European Cardiology Review)
Approximately one-half of patients undergoing diagnostic coronary angiography for angina have no significant coronary atherosclerotic stenosis. This clinical condition has recently been described as ischaemia with non-obstructive coronary arteries (INOCA). Coronary functional abnormalities are central to the pathogenesis of INOCA, including epicardial coronary spasm and coronary microvascular dysfunction composed of a variable combination of increased vasoconstrictive reactivity and/or reduced vasodilator function. During the last decade – in INOCA patients in particular – evidence for the prognostic impact of coronary functional abnormalities has accumulated and various non-invasive and invasive diagnostic techniques have enabled the evaluation of coronary vasomotor function in a comprehensive manner. In this review, the authors briefly summarise the recent advances in the understanding of pathophysiology and diagnosis of epicardial coronary artery spasm and coronary microvascular dysfunction.